The Influence of Building Features on Wayfinding by Adults with Intellectual Disability: Towards Achieving More Inclusive Building Design - Castell, Lindsay Maurice (Curtin University, 2017)
Wayfinding in buildings is a necessary activity for everyday living. This thesis observed and analysed the influence of built environment features on wayfinding success by adults with intellectual disability in comparison with typically developing adults. Analysis of results found that people with intellectual disability had greater difficulty in wayfinding. A wayfinding feature framework has been developed to show the relative influence of individual features on wayfinding success by adults with and without intellectual disability.